Metal-Free Activated Carbon Catalytic for Degradation of Organic Contaminants by Peroxydisulfate Activation - Prawiranegara, Barata Aditya; Setia Utama, Panca; Amri, Amun; Nurhayati; Muhdarina; Awaluddin, Amir; Saputra, Edy (Journal of Applied Materials and Technology, 2023)
Green chemistry has become trending recently, and the discovery of environmentally friendly catalysts is mandatory. Activated carbons (ACs) are one of the most environmentally friendly yet cheap materials that have the potential for catalyst application. Three commercially available ACs from Pancasari, Norit, and Chemical Supply were used as metal-free catalysts for advanced oxidation process (AOP) phenol removal in water in the presence of oxidants peroxydisulfate (PDS), and hydrogen peroxide (H2O2). It was found that ACs were effective to be used as catalysts for activating those oxidants to oxidize phenol in AOP reactions. In this study, the surface area of the catalyst significantly improved the phenol removal efficiency. ACs Pancasari (ACP) with the highest surface area has the best degradation performance of phenol removal with up to 99% removal efficiency in 60 minutes under the condition of [phenol] = 30 mg L-1, [ACP] = 0.2 g L-1, [PDS] = 3.3 mmol L-1, and T = 25oC. it was also found that the degradation process was significantly influenced by reaction temperature. Nevertheless, in this study, ACs display the potential as catalysts in the AOP process for wastewater treatments.